Self-similar solutions with fat tails for a coagulation equation with nonlocal drift - Herrmann, M; Laurencot, P; Niethammer, B (2009)
We investigate the existence of self-similar solutions for a coagulation equation with nonlocal drift. In addition to explicitly given exponentially decaying solutions we establish the existence of self-similar profiles with algebraic decay. To cite this article: M. Herrmann et al., C. R. Acad. Sci. Paris, Ser. I 347 (2009). © 2009 Académie des sciences.